Weighted Gene Co-expression Network Analysis Identifies Five Hub Genes Associated with Metastasis in Synovial Sarcoma - Wu, Hongzeng; Zhang, Benzheng; Zhao, Jiazheng; Zhao, Yi; Ma, Xiaowei; Feng, Helin (Combinatorial Chemistry & High Throughput Screening, 2022)
Background: Synovial Sarcoma (SS) refers to a malignant Soft Tissue Sarcoma (STS) which often comes about to children and adults and has a poor prognosis in elderly patients. Patients with local lesions can be treated with extensive surgical resection combined with adjuvant or radiotherapy, whereas about half of the cases have recurrent diseases and metastatic lesions, and five-year survival ratio is assessed within the range of 27% - 55% only. Methods: We downloaded a set of expression profile data (GSE40021) related to SS metastasis based on the Gene Expression Omnibus (GEO) database, and selected distinctly represented genes (DEGs) related to tumor metastasis. WGCNA was used to emphasize the DEGs related to tumor metastasis, and obtain co-expression modules. Then, the module most related to SS metastasis was screened out. The genes of enriched in this module were analyzed by Gene Ontology (GO) functional and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway improvement analysis. Cytoscape software was used for constructing protein-protein interaction (PPI) networks, and screening hub genes were made in virtue of Oncomine analysis. Result: We selected 514 DEGs, consisting of 210 up-regulated genes and 304 down-regulated genes. Through WGCAN, we got seven co-expression modules and the module most related to SS metastasis was turquoise module, which contained 66 genes. Finally, we screened out five hub genes (HJURP, NCAPG, TPX2, CENPA, NDC80) through CytoHubba and Oncomine analysis. Conclusion: In this study, we screened out five hub genes to help clinical diagnosis and serve as the latent purpose of SS treatment.
Keywords: WGCNA